Market orientation, innovation, and firm performance: An analysis of Albanian firms - Rezart Prifti; Genc Alimehmeti (Journal of Innovation and Entrepreneurship, 2017)
The purpose of this paper is to analyze the concept of market orientation as an outer source of innovation for organizations in the context of Albania. We investigate the market orientation relation with innovation and firm performance by analyzing a sample of 99 companies operating in Albania. The relationships and the impact of market orientation on innovation and performance is tested empirically through structural equation modeling techniques (SEM). The analysis confirms prior theoretical and empirical findings in developed economies, however, it gives way to some contextual interpretations. The implications of this study are considerable in academia and in managerial purposes. In academia, considering that there is no research in Albania on the topic of us being aware of, nevertheless, we identify the need for deeper and wider research, especially with bigger sample sizes, industry-specific, and across industries to grasp more about market reality. On managerial account, its relevance relies in the distinction of market orientation construct and the right division of components within the company, and the adequate approach toward intelligence generation, dissemination, and reaction on it by responding to market needs and competition with innovative products and services.
Keywords: O31; 650; Innovation; Market orientation; Intelligence generation; Intelligence dissemination; Performance